Weighing the influence of race and obesity on outcomes in patients with early‐stage breast cancer. Issue 6 (7th December 2020) - Taylor, Caitlin E.; Meisel, Jane Lowe
Abstract : The association between obesity and an increased risk of several cancers, including postmenopausal breast cancer, is well established. In this issue of Cancer, Nyrop et al evaluate disparities in obesity and the possible treatment implications of such disparities among Black and White women with early‐stage, hormone receptor–positive breast cancer. The authors highlight the importance of recognizing racial disparities among obesity trends and emphasize the need to address comorbidities early in breast cancer management for patients of all racial and ethnic backgrounds.